2016
DOI: 10.1038/srep35314
|View full text |Cite
|
Sign up to set email alerts
|

Altered T cell phenotypes associated with clinical relapse of multiple sclerosis patients receiving fingolimod therapy

Abstract: Multiple sclerosis (MS) is a T cell-mediated autoimmune disease. Fingolimod, a highly effective disease-modifying drug for MS, retains CCR7+ central memory T cells in which autoaggressive T cells putatively exist, in secondary lymphoid organs, although relapse may still occur in some patients. Here, we analyzed the T cell phenotypes of fingolimod-treated, fingolimod-untreated patients, and healthy subjects. The frequency of CD56+ T cells and granzyme B-, perforin-, and Fas ligand-positive T cells significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
4
17
0
Order By: Relevance
“…For this, ex vivo isolated PBMC from patients at baseline, 3, 6 and 12 months after treatment were stained for Granzyme B, as a marker of cytotoxic capacity [51]. As previously reported [52], we observed a dramatic increase in the frequency of Granzyme B + CD8 + T cells at all time points after treatment initiation, and this was statistically significant (Baseline: 12.5±3; 3 months: 41.4±6.9; 6 months: 46.9±5.8; 12 months: 46.8±5.7, Fig. 4).…”
Section: Increased Secretion Of Granzyme B By Cd8 + T Cells After Finmentioning
confidence: 99%
“…For this, ex vivo isolated PBMC from patients at baseline, 3, 6 and 12 months after treatment were stained for Granzyme B, as a marker of cytotoxic capacity [51]. As previously reported [52], we observed a dramatic increase in the frequency of Granzyme B + CD8 + T cells at all time points after treatment initiation, and this was statistically significant (Baseline: 12.5±3; 3 months: 41.4±6.9; 6 months: 46.9±5.8; 12 months: 46.8±5.7, Fig. 4).…”
Section: Increased Secretion Of Granzyme B By Cd8 + T Cells After Finmentioning
confidence: 99%
“…Moreno-Torres and colleagues 33 reported a higher pre-treatment CD56 bright NK cell frequency in patients who were subsequently stable versus active on FTY; a finding not replicated here. A cross-sectional study found higher CD56+ T-cell frequencies in FTY-treated versus untreated patients, and an even higher frequency of these cells during relapse in 4 patients 34 . We find CD56-expressing T-cell counts unaffected by FTY and confirm the resulting treatment-induced increase in their frequency.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, fingolimod-treated relapsed MS patients showed greater percentages of CD4 + T CM (and naïve cells) but not T EM , suggesting that CD4 + T CM may be involved in promoting relapses following fingolimod treatment in MS patients [192]. Furthermore, fingolimod treatment was associated with elevated frequencies of CD56 + memory T cells, and increased granzyme (GZM) B, perforin, and Fas ligand expression in memory T cells in MS patients, and interestingly, this T cell phenotype was also associated with clinical relapses [192]. Additionally, Herich et al demonstrated that CD4 + T EM expressing high levels of CCR5 and GZMK are involved in CNS immune surveillance in healthy individuals, but that this subset was dominant in peripheral blood mononuclear cells of MS patients, and that natalizumab (anti-α4-integrin) treatment significantly decreased these cells [193].…”
Section: Autoreactive T CM and T Em Subsets And Disease-modifying Thementioning
confidence: 97%
“…Subsequent studies showed that fingolimod affected primarily IL-17-producing CD4 + T CM [191]. Interestingly, fingolimod-treated relapsed MS patients showed greater percentages of CD4 + T CM (and naïve cells) but not T EM , suggesting that CD4 + T CM may be involved in promoting relapses following fingolimod treatment in MS patients [192]. Furthermore, fingolimod treatment was associated with elevated frequencies of CD56 + memory T cells, and increased granzyme (GZM) B, perforin, and Fas ligand expression in memory T cells in MS patients, and interestingly, this T cell phenotype was also associated with clinical relapses [192].…”
Section: Autoreactive T CM and T Em Subsets And Disease-modifying Thementioning
confidence: 99%